Islamic Defending Action And Fatwa Defenders Movement Indonesian Ulema Council - Fuad Muhsin; Hani Hanifah; Muhammad Hasan Al As Ari (UIN Sunan Gunung Djati Bandung, 2020)
TThe purpose of this study is to photograph the background of the birth of the National Movement for Defending Fatwa (GNPF) MUI and the methods used by the GNPF activist figures. By using social movement analysis and qualitative methods, this study successfully concluded that the GNPF-MUI and ABI are a consequence of the events and movements of group movements that occurred within the MUI, especially after the New Order. The existence of GNPF and ABI stems from the accommodating Islamist-puritan-conservative groups and tends to be revolutionary in the management of the 2015-2020 MUI. The strategy used by the GNPF actors was carried out by asking for support from revolutionary groups such as FPI to mobilize the period so that their actions receive sociological legitimacy from the Indonesian Muslim community